Malaysia’s foreign policy towards the Israeli-Palestinian conflicts : 1957-2014 - Nurul Norfatihah Md Yusoff,; Azlizan Mat Enh,; Al-Amril Othman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study discusses Malaysia’s stand and commitment in its foreign policy in the Israeli-Palestinian conflicts from 1957 to 2014. Malaysia’s foreign policy towards the Israeli-Palestinian conflicts is to prioritise security and stability in West Asia and the Middle East. A more critical aspect of Malaysia’s commitment is the liberation of the Palestinian land from the Zionist regime’s conquest and oppression, strongly supported by the major powers such as the United States and Britain. Although various peace negotiations have been held between Israel and Palestine, such concrete solutions have not been achieved adequately. The objective of this paper is to analyse the role of Malaysia in the Israeli-Palestinian conflicts from 1957 to 2014. This research uses qualitative methodology involving analysis of primary resources such as files, documents, Official Statements of Parliament of Malaysia, speech texts, and newspapers clipping from National Archive Kuala Lumpur and Tun Sri Lanang Library (PTSL). The result of this study proved that Malaysia had played a proactive and consistent role to seek a just and lasting solution to the Israeli-Palestinian conflicts.